2015
DOI: 10.1021/acs.inorgchem.5b01386
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of New Generation Cross-Bridged Bifunctional Chelator for 64Cu Radiotracers

Abstract: Bifunctional chelators have been successfully used to construct (64)Cu-labeled radiopharmaceuticals. Previously reported chelators with cross-bridged cyclam backbones have various essential features such as high stability of the copper(II) complex, high efficiency of radiolabeling at room temperature, and good biological inertness of the radiolabeled complex, along with rapid body clearance. Here, we report a new generation propylene-cross-bridged chelator with hybrid acetate/phosphonate pendant groups (PCB-TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Faster complexation is observed with N-phosphonic acid analogues, although heating is still necessary for the moment. 49,50,51,52 New linear systems such as H 2 DEDPA and H2AZAPA 53,54 as well as other type of macrocyclic ligands and cages (DiamSar 55,56,57 and its derivatives) offer good radiolabelling conditions at room temperature (Chart 2) and for some of them, a high degree of kinetic inertness. Bispidine derivatives (L 4 and L 5 , Chart 2) also form particularly stable Cu (II) complexes in vitro and in vivo.…”
Section: Chart 2 Structure Of Other Ligands Discussed In This Workmentioning
confidence: 99%
“…Faster complexation is observed with N-phosphonic acid analogues, although heating is still necessary for the moment. 49,50,51,52 New linear systems such as H 2 DEDPA and H2AZAPA 53,54 as well as other type of macrocyclic ligands and cages (DiamSar 55,56,57 and its derivatives) offer good radiolabelling conditions at room temperature (Chart 2) and for some of them, a high degree of kinetic inertness. Bispidine derivatives (L 4 and L 5 , Chart 2) also form particularly stable Cu (II) complexes in vitro and in vivo.…”
Section: Chart 2 Structure Of Other Ligands Discussed In This Workmentioning
confidence: 99%
“…This may be due to the relatively low copper concentration under radiolabelling conditions, or due to the formation of hydroxyl radicals by radiolysis which would not be present during "cold" complexation (Table 8). 122,123 3.2.2. Whilst the chelate required less than 5 minutes to achieve 100% radiolabelling, the peptide conjugate was 100% labelled in 30 minutes.…”
Section: First Generation 64 Cu Chelatorsmentioning
confidence: 99%
“…A new generation of propylene-cross-bridged chelators with hybrid acetate/phosphonate pendant groups (PCB-TE1A1P) ( Figure 4 ) has been developed to improve the in vivo stability and fast clearance. PET analysis in mice confirmed that PCB-TE1A1P has good potential as a bifunctional chelator for 64 Cu-based radiopharmaceuticals, especially those based on peptides [ 109 ].…”
Section: Spacers Chelators and Radionuclidesmentioning
confidence: 99%